Fluorescence properties of demineralized enamel after resin infiltration and dental bleaching - Torres, Carlos Rocha Gomes [UNESP]; Zanatta, Rayssa Ferreira [UNESP]; Da Fonseca, Beatriz Maria [UNESP]; Borges, Alessandra Bohler [UNESP] (My University, 2019)
Purpose: To evaluate the effects of different white spot lesion (WSL) treatments associated with dental bleaching on the fluorescence of dental enamel. Methods: 80 flat enamel disks (3 mm diameter and 1 mm thick) were obtained from bovine incisors. The initial fluorescence (fluorescent emission or Delta E ab-FL units) of the specimens was measured using a spectrophotometer. Artificial caries was created in all specimens, and the measurements were repeated. The specimens were divided into four groups according to the treatment applied (n = 20): CON (control)-immersion in ultrapure water for 8 weeks; SAL-immersion in artificial saliva for 8 weeks; FL-daily application of 0.05% sodium fluoride for 1 minute/artificial saliva for 8 weeks; and ICON-resin infiltration (Icon). After the treatments, the assessments were repeated. Dental bleaching using 35% hydrogen peroxide gel was performed on all specimens for 30 minutes, and the measurements were made again after 7 days. Data were submitted to ANOVA and Tukey tests across the treatments for each moment of evaluation. Results: Fluoride and saliva remineralization were not able to change enamel fluorescence, even after bleaching. Only resin infiltration increased the enamel fluorescence; however, after bleaching, all groups presented similar values. Icon increased translucency immediately after application, but bleaching reduced it to its initial values. (Am J Dent 2019;32:43-46).